Comparison of Enzymatic and Microbiological Gentamicin Assays - Smith, Arnold L. (1974)
The correlation coefficient between the rapid enzymatic and the overnight microbiological assays for 211 urine and serum specimens was 0.96. The 95% confidence limits yielded a correlation coefficient between 0.92 and 0.98. Both methods tended to underestimate the amount of a gentamicin added to urine. When only serum samples were considered, the predicted value obtained from the linear regression analysis of either method was within 0.57 μg/ml 99% of the time. This high degree of positive correlation will permit safe rapid adjustment of individualized patient gentamicin dosages.